Peripheral blood lymphocyte subpopulations in patients following small diameter metal-on-metal total hip replacement at long-term follow-up - Reiner, Tobias; Heilemann, Hester; Tripel, Elena; Rosshirt, Nils; Sorbi, Reza; Nees, Timo A.; Gotterbarm, Tobias; Merle, Christian; Moradi, Babak; Hagmann, Sébastien (Journal of Clinical Medicine, 2020)
(1) Background: The objective of the present study was to investigate peripheral blood lymphocyte subpopulations in patients with small diameter metal-on-metal total hip arthroplasty (MoM THA) and elevated blood metal ion concentrations at long-term follow-up. The hypothesis was that increased blood metal ion levels or the presence of adverse local tissue reactions (ALTR) would be associated with changes in the peripheral expression of lymphocyte subpopulations, which could potentially serve as early diagnostic markers for metal wear related complications. (2) Methods: Peripheral blood samples were analyzed for leucocyte subgroups (CD3+, CD4+, CD8+, CD14+, CD16+/CD56+, CD25+/CD127−, CD19+, IFN-γ+, IL-4+ and IL-17A+ cells) in 34 patients with elevated blood metal ion levels (combined cobalt and chromium levels >2 µg/L) following small head MoM THA at a mean follow-up of 15.6 years. Fifteen patients with small head MoM THA and blood metal ion levels within the normal range and 15 patients with conventional ceramic-on-polyethylene THA served as control groups. In addition, blood metal ion levels and leucocyte subpopulations were compared between patients with and without adverse local tissue reactions (ALTR), which was investigated by MRI in 27 patients of the study cohort. (3) Results: There was a significant decrease in the levels of IFN-γ+ Type-1 T helper cells (Th1) in patients with MoM THA compared to the ceramic-on-polyethylene control group (p < 0.001). No statistically significant differences in the cell counts of other lymphocyte subpopulations were found between the three groups. Cobalt ion levels were significantly higher in patients with ALTR (p < 0.001) compared to the non-ALTR group, but no differences in the levels of lymphocyte subsets were found between the two groups. (4) Conclusions: No adverse systemic effects with respect to peripheral blood leucocyte subpopulations could be detected in the present study in patients following THA with a small diameter MoM articulation at long-term follow-up. We found a significant decrease of IFN-γ+ Th1 cells in patients with MoM THA compared to the control group, but no differences in the peripheral expression of leucocyte subpopulations were seen between patients with and without ALTR. Future studies with larger patient cohorts and additional histopathological investigations could help to better understand the role of Th1 cells and other cell lines of the adaptive immune system in the development of metal wear related complications after total joint replacement.